2016
DOI: 10.1002/bjs.10052
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from trauma haemorrhage and opportunities for improvement in transfusion practice

Abstract: There is a high burden of trauma haemorrhage that affects all age groups. Research is required to understand the reasons for death after the first 24 h and barriers to timely transfusion support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 24 publications
(20 reference statements)
6
81
0
2
Order By: Relevance
“…These findings are supported by a recently published study from the UK investigating transfusion practices in traumatic haemorrhage -the median time to delivery of cryoprecipitate as part of a MHP was more than 2 hours and almost 50% of patients did not receive cryoprecipitate as part of their initial resuscitation (54). This is concerning, considering that the median time to death from haemorrhage is reported to be approximately 2.6 hours (48) (54).…”
Section: Fibrinogen Replacement As Part Of a Mhpsupporting
confidence: 55%
See 1 more Smart Citation
“…These findings are supported by a recently published study from the UK investigating transfusion practices in traumatic haemorrhage -the median time to delivery of cryoprecipitate as part of a MHP was more than 2 hours and almost 50% of patients did not receive cryoprecipitate as part of their initial resuscitation (54). This is concerning, considering that the median time to death from haemorrhage is reported to be approximately 2.6 hours (48) (54).…”
Section: Fibrinogen Replacement As Part Of a Mhpsupporting
confidence: 55%
“…The impressive delivery of blood component therapy as described in the PROPPR trial may be difficult to translate into routine clinical practise (53). A recent study from Stanworth et al reports widespread variations in patterns of blood product delivery across a number of trauma centres, with few patients receiving an 'optimal' product ratio (54).…”
Section: Major Haemorrhage Protocols (Mhp)mentioning
confidence: 99%
“…A number of studies have reported that the fixed-ratio MHP is ineffective in maintaining adequate fibrinogen levels [24, 37]. Additionally there can be significant time delays to Cryo transfusion and a large proportion of patients do not receive Cryo as part of a fixed-ratio MHP [38, 39]. The CRYOSTAT trial has shown that it is feasible to utilise Cryo empirically as part of a fixed-ratio MHP; however, the median time to transfusion was still 60 min [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, a national study prospectively evaluated transfusion practice in trauma hemorrhage, including fibrinogen supplementation at 22 trauma centers (major trauma centers and trauma units) between 2009 and 2011. 32 The median time to cryoprecipitate transfusion was 156 minutes at a major trauma center (184 minutes in a trauma unit), by which time 50% of patients had died. Although the reasons for delays in cryoprecipitate transfusion were not collected as part of this study, this is an important area where further work is needed to better understand the barriers to timely transfusion support.…”
Section: Acquired Hypofibrinogenemiamentioning
confidence: 99%
“…45 Despite this, specific fibrinogen replacement appears late in current major hemorrhage transfusion therapy as seen in observational and prospective studies, eg, PROPPR and PROMMT studies. 32,46,47 A potential reason for the late administration of cryoprecipitate is the time taken for preparation and thawing (in some centers there is additional time required for pooling of the individual cryoprecipitate units).…”
Section: Traumamentioning
confidence: 99%